Psychological insights for understanding COVID-19 and families, parents, and children - Bornstein, Marc H. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
With specially commissioned introductions from international experts, the Psychological Insights for Understanding COVID-19 series draws together previously published chapters on key themes in psychological science that engage with people's unprecedented experience of the pandemic. This volume collects chapters that address prominent issues and challenges presented by the SARS-CoV-2 pandemic to families, parents, and children. A new introduction from Marc H. Bornstein reviews how disasters are known to impact families, parents, and children and explores traditional and novel responsibilities of parents and their effects on child growth and development. It examines parenting at this time, detailing consequences for home life and economies that the pandemic has triggered; considers child discipline and abuse during the pandemic; and makes recommendations that will support families in terms of multilevel interventions at family, community, and national and international levels. The selected chapters elucidate key themes including children's worry, stress and parenting, positive parenting programs, barriers which constrain population-level impact of prevention programs, and the importance of culturally adapting evidence-based family intervention programs. Featuring theory and research on key topics germane to the global pandemic, the Psychological Insights for Understanding COVID-19series offers thought-provoking reading for professionals, students, academics, policy makers, and parents concerned with the psychological consequences of COVID-19 for individuals, families, and society.
OCLC-licensed vendor bibliographic record.
Keywords: COVID-19 (Disease) -- Psychological aspects; COVID-19 (Disease) -- Social aspects; Families -- Psychological aspects; FAMILY & RELATIONSHIPS / General; FAMILY & RELATIONSHIPS / Life Stages / Adolescence; FAMILY & RELATIONSHIPS / Life Stages / Infants & Toddlers